Organology Analysis of Dol Musical Instruments as a Mathematics Learning Media Based on the Local Wisdom of Bengkulu in Elementary School - Parmadi, Bambang; Dalifa, Dalifa; Agusdianita, Neza; Syaqki Parmadie, Aliffarazzi (KnE Social Sciences, 2024)
The research was held back by the unique background of the Dol instrument as ritual music at the ceremony of the Tabut and the identity of the Bengkulu traditional music. The purpose of the study is to describe the organology of the Dol instrument and its method of production and describe the design of the implementation of musical instruments on mathematics learning materials in elementary schools in both physical and sociocultural detail. The theory used is ethnomusicology and mathematics learning media. The method used is case analysis, which requires a qualitative and quantitative descriptive approach to the organology of the Dol musical instrument and learning media. The data sources used are their sources and a validator with observation techniques interview techniques, and documentation techniques. The validity of data uses their types of triangulation (technique, source, and time). The result of this research was either a text box or a materials module. The result of the Dol instrument’s organological analysis as a media learning mathematics based on local cultural wisdom at the elementary school is expected to assist every teacher in educating students in understanding the preservation of local culture and implanting the local area’s cultural arts character. Besides, the results of this study will contribute to the literacy and media sources of common education and general education. Keywords: bengkulu, dol musical instruments, elementary school, local wisdom, mathematics learning media, organology analysis.